The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
Rumen Microbiology: From Evolution to Revolution 2015
DOI: 10.1007/978-81-322-2401-3_1
|View full text |Cite
|
Sign up to set email alerts
|

Rumen Microbiology: An Overview

Abstract: The systematic exploration of microbial ecosystem of the rumen was commenced by the father of rumen microbiology, Robert Hungate, in 1950s. His contributions toward the development of anaerobic culture techniques have illustrated the ways to explore the complex microbial structures of the rumen and other anaerobic ecosystems. The understanding of rumen microbiology has strengthened an awareness to improve the feed utilization and manipulation of microbial compositions. Microbes and their interactions in inters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 117 publications
3
41
0
2
Order By: Relevance
“…Bacterial population in the rumen of domestic cattle occurs at a concentration of 10 10–11 cells/g of rumen content [34], while other authors reported a total count of 10 9 in red deer [35,36]. Our results show a concentration of anaerobic and aerobic bacteria in a range of 10 5–6 cells/g.…”
Section: Discussionsupporting
confidence: 43%
“…Bacterial population in the rumen of domestic cattle occurs at a concentration of 10 10–11 cells/g of rumen content [34], while other authors reported a total count of 10 9 in red deer [35,36]. Our results show a concentration of anaerobic and aerobic bacteria in a range of 10 5–6 cells/g.…”
Section: Discussionsupporting
confidence: 43%
“…Diets with high energy and protein levels in Group H effectively promoted the growth performance and carcass characteristics of goats [ 24 ]. Meanwhile, the digestion and absorption of these diets were closely related to the rumen bacteria [ 5 ]. A previous study reported that the changes in the ruminal microbiota could promote the ADG of goats [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rumen is a complex microbial ecosystem in ruminants. It can ferment feedstuffs to volatile fatty acids, microbial proteins, and vitamins, which play important roles in animal health and production [ 4 , 5 ]. Sometimes, it has to deal with lower quality fodder or silage [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rumen microbes are classified into 3 domains: bacteria, archaea (methanogens), and eucarya (protozoa and fungi). There are more than 200 species of rumen bacteria and their population range is 10 10 to 10 11 per g. Anaerobic fungi in the rumen are classified into 6 genera with the range population of 10 3 to 10 6 per g, rumen methanogen population is up to 10 9 per g, while bacteriophage and ciliate protozoa having population ranges of 10 7 to 10 9 per g and 10 4 to 10 6 per g, respectively ( Choudhury et al., 2015 , Kumar et al., 2009 , Wanapat, 2000 ). Bacteria population are most actively involved in the plant fibre degradation, as revealed by the fact that bacteria associated with feed particles account for nearly 50% to 75% of the total microbial population ( Minato et al., 1966 ).…”
Section: Digestive Physiology Of Rumenmentioning
confidence: 99%